Desensitization in Crossmatch-positive Kidney Transplant Candidates. Issue 2 (5th August 2022) - Noble, Johan; Jouve, Thomas; Malvezzi, Paolo; Rostaing, Lionel
Abstract : Access to kidney transplantation is limited by HLA-specific sensitization. Desensitization strategies enable crossmatch-positive kidney transplantation. In this review, we describe clinical experience gained over the last 20 y using desensitization strategies before kidney transplantation and describe the different tools used (both drugs and apheresis options), including IVIg, rituximab, apheresis techniques, interleukin-6 interference, proteasome inhibition, enzymatic degradation of HLA antibodies, complement inhibition, and B cytokine interference. Although access to transplantation for highly sensitized kidney transplantation candidates has been vastly improved by desensitization strategies, it remains, however, limited by the recurrence of HLA antibodies after transplantation and the occurrence of antibody-mediated rejection.